The Relationship Between Children and Their Maternal Uncles: A Unique Parenting Mode in Mosuo Culture - Xiao, Erping; Jin, Jing; Hong, Ze; Zhang, Jijia (Frontiers in Psychology, 2022)
The relationship between children and their maternal uncles in contemporary Mosuo culture reveals a unique parenting mode in a matrilineal society. This study compared the responses of Mosuo and Han participants from questionnaires on the parent-child and maternal uncle-child relationship. More specifically, Study 1 used IPPA to assess the reactions of the two groups to the relationship between children and their mothers, fathers, and maternal uncles. The results show that while Han people display a higher level of attachment towards their fathers than their maternal uncles, Mosuo people do not exhibit a significant difference in this aspect. Study 2 used a scenario-based method to compare how adults and teenagers perceive the rights and responsibilities of fathers/maternal uncles towards their children/nephews or nieces. The results show that Han adults attribute more rights and responsibilities to their own children than nephews/nieces while their Mosuo counterparts have the reverse pattern and assign stronger responsibilities to their nephews/nieces than their own children. Both groups perceive the fathers to be the bearer of rights and responsibilities, although this perception was weaker among Mosuo. This paper concludes that in the Mosuo society, fathers have a relatively weak social role as a result of their unique matrilineal social structure.